Filogeografia de populações naturais do buriti (Mauritia flexuosa L. f., Arecaceae) do Brasil Central - Lima, Natácia Evangelista de (2012)
Mauritia flexuosa, popularly known as buriti, is a large palm that occurs especially in association with wetlands (veredas) in South America. It is distinguished because of its economic importance for local populations from Central Brazil, and as source of food, breeding site and haven for the terrestrial and aquatic fauna. The effect of historical demographic events and climatic fluctuations in the current distribution of buriti can provide clues about the responses of this species to anthropic pressures and to future climatic changes. For this purpose we studied the phylogeography of M. flexuosa. The results were based on the differences of sequences from the following chloroplast intergenic regions: psbA-trnH, trnC-ycf6 and trnS-trnG. We sampled 170 individuals from 14 localities throughout Central Brazil, including populations in the Amazon, Araguaia/Tocantins, Paraná and São Francisco Basins. Since the distribution of M. flexuosa is restricted to wetlands, which are surrounded by large areas of dry lands that may act as barriers to gene flow, we hypothesized that populations are highly differentiated and that River Basins act as phylogeographic breaks. The combined data from the three sequence regions generated a fragment of 1205bp, with 11 haplotypes. Nucleotide diversity was low (π = 0.005314 +/- 0.002800) and haplotipic diversity was high (h =0,791) for the combined data. The population parameter θ, and nucleotide and haplotype diversity per population, shows a pattern where populations from different geographic regions have a relative genetic uniformity, separated by steep losses on the diversity; what characterizes colonization by sectors. Differentiation among populations was significant (P< 0.001), but no sign of recent bottleneck on population size followed by expansion was found (D Tajima=-1.955 p = 0.00210; Mismatch Distribution=0.034 p=0.7467 and growth parameter g=402. 402, 95% = -334.961 ICredi, ICreds 95% = 999.91). We could group populations by location in the phylogenetic analysis (Network software), but they do not support the initial hypothesis that the major basins act as important phylogeographic breaks for the distribution of maternal lineages of M. flexuosa. The studied populations showed ancient time of coalescence. This research provided more details on the dynamics and genetic structure of the remnant of buriti populations, helping to elucidate the evolutionary history of this neotropical palm.